Senescent Fibroblasts Enhance Early Skin Carcinogenic Events via a Paracrine MMP-PAR-1 Axis - Malaquin, Nicolas; Vercamer, Chantal; Bouali, Fatima; Martien, Sébastien; Deruy, Emeric; Wernert, Nicolas; Chwastyniak, Maggy; Pinet, Florence; Abbadie, Corinne; Pourtier, Albin (PloS one, 2013)
The incidence of carcinoma increases greatly with aging, but the cellular and molecular mechanisms underlying this correlation are only partly known. It is established that senescent fibroblasts promote the malignant progression of already-transformed cells through secretion of inflammatory mediators. We investigated here whether the senescent fibroblast secretome might have an impact on the very first stages of carcinogenesis. We chose the cultured normal primary human epidermal keratinocyte model, because after these cells reach the senescence plateau, cells with transformed and tumorigenic properties systematically and spontaneously emerge from the plateau. In the presence of medium conditioned by autologous senescent dermal fibroblasts, a higher frequency of post-senescence emergence was observed and the post-senescence emergent cells showed enhanced migratory properties and a more marked epithelial-mesenchymal transition. Using pharmacological inhibitors, siRNAs, and blocking antibodies, we demonstrated that the MMP-1 and MMP-2 matrix metalloproteinases, known to participate in late stages of cancer invasion and metastasis, are responsible for this enhancement of early migratory capacity. We present evidence that MMPs act by activating the protease-activated receptor 1 (PAR-1), whose expression is specifically increased in post-senescence emergent keratinocytes. The physiopathological relevance of these results was tested by analyzing MMP activity and PAR-1 expression in skin sections. Both were higher in skin sections from aged subjects than in ones from young subjects. Altogether, our results suggest that during aging, the dermal and epidermal skin compartments might be activated coordinately for initiation of skin carcinoma, via a paracrine axis in which MMPs secreted by senescent fibroblasts promote very early epithelial-mesenchymal transition of keratinocytes undergoing transformation and oversynthesizing the MMP-activatable receptor PAR-1.